Effects of interferon-gamma and tumour necrosis factor-alpha on the development of cytotoxic T lymphocytes in autologous mixed lymphocyte tumour cultures with human melanoma. - Roth, A D (1991)
We have studied the influence of tumour necrosis factor-alpha (TNF-alpha) and interferon-gamma (IFN-gamma) on the development of cytotoxic T lymphocytes (CTL) against melanoma in mixed lymphocyte tumour cultures (MLTC). In these MLTC, TNF-alpha at 10(4) U/ml increased the expansion of the CTL up to 10(4)-fold over recombinant IL-2 (rIL-2) alone. IFN-gamma at 10(4) U/ml and combinations of TNF-alpha plus IFN-gamma at 10(2)-10(3) U/ml promoted the proliferation more variably. MLTC generated with rIL-2 showed a predominance of CD8+ cells, while 2 weeks of culture in the presence of IFN-gamma at 10(4) U/ml, or with IFN-gamma and TNF alpha at 1 x 10(2)-10(3) U/ml, favoured the emergence of CD4+ cell populations. The cytotoxic activity of the lymphocytes generated in these MLTC showed a consistent decline of K562 cytotoxic activity following exposure to the combination of IFN-gamma and TNF-alpha. Despite the altered T cell subset distribution with different combinations of cytokines, no consistent alteration in the specific anti-tumour cytotoxicity against melanoma was detected. These results suggest that TNF-alpha and IFN-gamma influence the activation, phenotypic, and functional outcome of MLTC-generated CTL, and may account for the phenotypic variations observed in T cell populations generated in vitro.